2021
DOI: 10.1016/j.amjoto.2021.103162
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in healthcare services during the COVID-19 pandemic: Patient screening based on symptoms is an effective strategy for avoiding delayed laryngeal cancer diagnosis

Abstract: Objective Restriction in healthcare services during the COVID-19 pandemic caused delays in the diagnosis and treatment of several diseases. To overcome the risk of missed diagnosis of head and neck cancers, before deleting the scheduled appointments, we have introduced a selection of the patients by examining the clinical presenting issue and previous medical history. The aim of this study is to show the effects of the abovementioned strategy on the diagnosis and management of laryngeal cancer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…The virus was initially underestimated in Italy, which led to an emotional efficiency to overcome the outbreak, diverting attention away from cancer patients. 4,6,28…”
Section: Discussionmentioning
confidence: 99%
“…The virus was initially underestimated in Italy, which led to an emotional efficiency to overcome the outbreak, diverting attention away from cancer patients. 4,6,28…”
Section: Discussionmentioning
confidence: 99%
“…Murri et al evaluated the numbers of laryngeal SCC patients during the pandemic and compared them with the patients attended before the pandemic [ 11 ]. The authors concluded that there were 19 laryngeal cancers in the post-pandemic group and 25 patients in the before the pandemic group.…”
Section: Discussionmentioning
confidence: 99%
“…No significant differences were observed regarding the tumor stage between the study groups. However, they reported an increase in the time between cancer diagnosis and surgical treatment [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The drastic reduction of the routine activity of otolaryngology units had a dramatic impact on the services offered to patients during the pandemic. Scheduled visits and elective surgeries were postponed; this situation, associated with the patients’ fear to contract the infection inside the hospital, led to a delay in the diagnosis and treatment of several diseases, including head and neck cancer, with a dangerous shift toward more advanced cancer stages and potential upstaging of TNM classification 26 , 27 .…”
Section: Impact Of Covid-19 On Otolaryngological Activitymentioning
confidence: 99%
“…To reduce the risk of missing or delayed oncological diagnosis, oncology centres began performing a selection of scheduled visits by examining the symptoms reported and previous medical history 26 . The most frequent criteria found in the literature to select patients were history of malignant cancer, dysphonia and persistent dysphagia, cervical masses of new onset, dyspnoea, recent body weight loss and bleeding from the upper aerodigestive tract.…”
Section: Risk Of Contagion In Otolaryngology Specialistsmentioning
confidence: 99%